New evidences on groundwater dynamics from the Souss-Massa system (Morocco): Insights gained from dissolved noble gases. (October 2019) - Hssaisoune, Mohammed; Bouchaou, Lhoussaine; Matsumoto, Takuya; Araguas, Luis; Kraml, Michael; Aggarwal, Pradeep
Abstract: The Souss-Massa plain, an important agriculture area of the Middle Western of Morocco, is a depression zone filled with Plio-Quaternary sediments which are overlying a complex multi-layered sedimentary basement. Over the last decades, population growth, agriculture development and recurrent droughts have been increasing the pressure on the aquifers of the region. The shallow aquifer is intensively exploited. About 94% of the water resources in the basin are used for agriculture. Groundwater levels show a general, continuous depletion. Chemical tracers indicate a progressive deterioration of groundwater quality in many areas with multiple sources of salinity. Another consequence of overexploitation and water use for agriculture is the increase of nitrate concentrations in groundwater. This multiple isotope investigation ( 18 O, 2 H, 14 C, 3 H, noble gases) confirms that the aquifer is mainly recharged by waters derived from the High Atlas Mountains, where the precipitation rate is higher than in the study area. The spatial variations of stable and radioactive isotope concentrations indicate that active mixing of recently recharged and old groundwater within the aquifer system. The recent recharge is observed mainly along the Souss River and in the irrigated areas. The evolution of the fluids can be observed on a locale scale in the 3 He/ 4 He ratios, which are largely controlled by the amount of 4 He, indicating the addition of terrigenic He to groundwater and/or mixing processes. The finding of mantle helium signature in shallow aquifer generally supports the assumption of the deep, permeable faults in the area of the Souss depression (El Klea and Biougra faults). This study indicates the extent of groundwater renewability and allows establishing a scientifically-based water management model for sustainable exploitation of water resources in the Souss-Massa basin. Graphical abstract: Image 1 Highlights: Role of radioisotopes to study groundwater age in a complex system in arid climate. The contribution of the noble gas tracers indicates the mixing process. Dissolved noble gases are useful to confirm the vulnerability of groundwater system.